166 CHILD MALTREATMENT TRAINING AND KNOWLEDGE AMONG PEDIATRIC, EMERGENCY MEDICINE, AND FAMILY MEDICINE RESIDENTS. (1st January 2005) - Edwards, H.; Starling, S. P.; Heisler, K.
Abstract : Introduction: Despite the steady rise in the prevalence of child abuse over the past 20 years, the training of physicians and residents in the assessment of physical and sexual abuse remains inadequate. Resident training is not standardized across the U.S. and comprehensive child maltreatment curricula are available only among a limited number of programs throughout the country. Data regarding the quality and quantity of current training and its impact on resident knowledge and skills are lacking. The goal of this study was to assess the training, comfort, and knowledge related to the medical management of child maltreatment among pediatric, emergency medicine (EM), and family medicine (FM) residents. Methods: A 25-item anonymous survey was distributed to approximately 118 pediatric, EM, and FM residents from five residency programs at one medical school in southeastern Virginia. Surveys were completed by 75 residents for a return rate of 64%. Results: There were significant differences in training and knowledge across all three specialties, with pediatric residents consistently outperforming their colleagues in EM and FM. Eighty-one percent of all residents were not able to correctly identify three anatomic structures from a color photograph of female genitalia. Other significant findings will be reviewed, along with plans for expanding the scope of this study and its implications for future resident education. Conclusions: Residents' training and knowledge related to the medical management of child abuse remain highly variable by specialty. Statewide and national data are needed in order to develop a more comprehensive picture of the extent and effectiveness of residency training in the area of child maltreatment. The availability of such data will facilitate efforts toward the development of a standardized curricula in child maltreatment for residency programs throughout the United States.